Comparative Study Of Wall Mapping Plan Using Gravitation and Kantilever in The Mulyorejo River Ngantang District of Malang - Hoto, Wilibaldus; Suhudi, Suhudi; Arifianto, Andy Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT The retaining wall is a major component of the main building structure for highways and other environmental buildings related to contoured soils or soils of different elevations. Briefly the retaining wall is a wall built to hold the mass of the ground above the structure or building that is created. There are several types of retaining wall which are often used in building construction such as gravity retaining wall, cantilever retaining wall, counter contrast wall, and butter retaining wall, which is used in this research is gravity and cantilever type retaining wall by using stone pairs. The purpose of this study is to compare the time and cost required. Dimensions of the gravity-type retaining wall with a length of (b) 29 meters and height (h) = 9 meters, the upper width (B1) = 0.50 meters, bottom width (B2) = 2.50 meters, 60 days required time, and Planned cost Rp. 482.887.930. Dimensions of cantilever type wall with length (b) 29 meters and height (h) = 9 meters, upper width (B1) = 0.40 meters, bottom width (B2) = 2.50 meters, 72 days required, and Planned cost Rp. 405.801.38. Keywords: comparison ; retaining wall ; gravity and cantilever.